Manajemen Proyek Sistem Informasi - Agung Wijoyo; Rizki Reza Utama; Muhamad Mahmud; Fuji Ubaydillah; Sinta Rahmawati; Muh. Tantowi Alhabas (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Information system project management is an activity of available resources from an information system solution development project so that a solution system can be produced that meets the stated objectives. Information system project resources referred to here include human resources, work equipment and facilities (both hardware and software), funds, and logistics. Information systems project management controls three aspects of an information systems project, namely product, time, and cost. Products produced by information system projects are determined to have features according to design, meet predetermined performance limits and are easy to maintain. “The project must be completed within a predetermined timeframe with a tolerable level of success and cost according to the budget.